The Effects of 12 Weeks In-Water Training in Stroke Kinematics, Dry-Land Power, and Swimming Sprints Performance in Master Swimmers - Espada, Mario C.; Santos, Fernando J.; Conceicao, Ana; Louro, Hugo; Ferreira, Catia C.; Reis, Joana F.; Pessoa-Filho, Dalton M. [UNESP]; Pereira, Ana (Imr Press, 2022)
Background: Master swimming is becoming increasingly popular, but research related to the training process and its effect on this population is scarce. The aim of this study was to investigate the effects of 12 weeks in-water training in stroke kinematics, dry-land power, and swimming sprints performance in master swimmers, and the relationships between these variables in this sports population. Methods: 15 healthy and physically active male master swimmers (age 32.3 +/- 5.1 years, height 1.81 +/- 0.04 m, body mass 77.0 +/- 6.5 kg, training experience of 11 +/- 4 years and average swimming training volume similar to 2.5 km/day, 3 times a week) participated in the study. Previously and alter the intervention program, entirely water-based, swimmers were tested in a dry-land environment to assess their upper and lower body limbs (UL and LL) strength through power measurements, namely countermovement jumps (CMJ), seated 3 kg medicine ball throwing (MBT) and maximal isometric strength with handgrip (HG). In-water 50 m maximal front crawl swimming test was also completed. Swimming performance at 15, 25, and 50 m (T-15, T-25, and T-50) was determined, and the associated stroke kinematics. During the intervention program period, swimming training comprised three sessions per week (7.5 +/- 0.9 km per microcycle), with low-to high-intensity aerobic and anaerobic swimming series and technical drills. Results: T-25 significantly decreased after 12 weeks of training (18.82 +/- 2.92 vs. 18.60 +/- 2.87 sec, p = 0.02), the same was observed in the case of T-50 (40.36 +/- 7.54 vs. 38.32 +/- 6.41 sec, p = 0.00). Changes in stroke rate (SR), stroke length (SL) and stroke index (SI) in swimming performance at 15 m were not observed, contrarily to 25 and 50 m. where SL and SI significantly increased. MBT and HG improved, but not CMJ, and improvements in T-15, T-25 and T-50 were mostly related to kinematic proficiency improvement. Conclusions: 12 weeks of in-water training in master swimmers significantly enhance performance time in 25 and 50 m front crawl swimming. SL and SI are also improved and are the variables that most influence T-15, T-25 and T-50 when compared to SR and dry-land power variables. Centering the training process not only in in-water tasks in master swimmers seem to be of relevant interest since age influences stroke kinematic and power variables.
Keywords: Aging; Aquatic sport; Biomechanics; Strength; Speed